PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PEMBERDAYAAN KARYAWAN DAN INOVASI ORGANISASI PADA MOZZARELLA RESTAURANT - Surya Gunawan, Wayan; Ketut Surya, Ida Bagus (E-Jurnal Manajemen, 2015)
This research was conducted in Mozzarella Restaurant & Bar Legian Bali. The number of samples examined as many as 117 employees, with the method of determining the saturated sample. The purpose of this study was to determine the effect of transformational leadership on employee empowerment and organizational innovation. Data was collected by using a questionnaire and indicators were measured using a Likert scale. The data analysis technique used is the path analysis (path analysis). The analysis showed that transformational leadership has positive influence on employee empowerment and organizational innovation by 73.63 percent, while the remaining 26.37 percent influenced by other factors that are not included in the model. This means that by implementing transformational leadership, the leadership of Mozzarella Restaurant and Bar Legian Bali can empower their employees and the employees who have been empowered expected to create new innovations for the development of the company Mozzarella Restaurant & Bar Legian Bali.
Keywords: Organizational Innovation, Employee Empowerment, Leadership Transformational